Telemedicine: A Growing Need during the COVID-19 Pandemic - Banu, Shastha; Aryal, Bhagwan; Mathema, Sujala; Joshi, Bhagarathi (International Research Journal of MMC, 2024)
The world has been facing an enormous challenge to cope with containing the coronavirus disease-2019 (COVID-19), be it alone with vaccinations or innovative ways to help people get treated. Telemedicine is one such boon for people to get some help during COVID-19. The purpose of this study was to identify the growing demand for telemedicine, investigate its use in various nations, and assess its strengths, difficulties, and prospects in the Nepalese context. This paper took a narrative descriptive technique, using Google, Google Scholar, and Pubmed as key search engines from January to February 2024, to investigate the growing need for telemedicine in emergencies, its worldwide use, and its application in Nepal. It searches for related material using keywords such as "telemedicine", "telehealth", "COVID-19", and "Nepal". The COVID-19 pandemic has accelerated the development of telemedicine, with patients and healthcare professionals expressing satisfaction with visits. The pandemic has prompted increased use of telemedicine, telepharmacy, teledermoscopy, artificial intelligence, and robotic machines, requiring collaboration between national and individual groups. Telemedicine's economic sustainability is threatened by increased private practitioners, potential fees, low adoption rates, lack of legal frameworks, and inadequate health facilities in developing countries, necessitating further research on visit-related factors and patient-provider connections.